Analysis of the Dimensions of Gender Justice in the Process of Appointing Managers: A Case Study in the Welfare Organization of Fars Province - Jamshidi , Ali; Gholami Chenarestan Olya, Abdolkhalegh; Pirzad , Ali (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2026)
Objective: This study aimed to analyze the dimensions of gender justice in the process of appointing managers in the Welfare Organization of Fars Province and to develop a qualitative model of fair and merit-based managerial appointment. Methods and Materials: This study was conducted using a qualitative research design based on the grounded theory approach. The research participants included 15 managers, experts, and informed organizational actors in the Welfare Organization of Fars Province who had direct knowledge or practical experience regarding managerial appointment, promotion procedures, organizational justice, and gender-related challenges in administrative advancement. Participants were selected through purposive sampling, and data collection continued until theoretical saturation was achieved. Data were collected through semi-structured interviews focused on managerial appointment criteria, gender justice in promotion, organizational barriers, supportive policies, and contextual conditions affecting women’s access to leadership positions. The interview data were transcribed and analyzed through open, axial, and selective coding. Findings: The inferential analysis of the qualitative data showed that managerial competency indicators formed the central phenomenon of the extracted model. These indicators included leadership skills, decision-making ability, specialized background, and professional experience. Organizational justice and gender justice were identified as causal conditions influencing fair appointment. Organizational justice consisted of distributive, procedural, and interactional justice, while gender justice included equal opportunities for promotion, removal of mental and structural barriers for women, gender-oriented policies and supports in appointments, and employees’ perception of gender discrimination. Contextual and environmental factors, including organizational culture, attitudes of senior managers, higher-level laws and regulations, and lived experiences of female managers, were identified as background conditions shaping the realization of gender justice in managerial appointment. Conclusion: The results indicated that gender justice in managerial appointment is achieved when competence-based evaluation is combined with transparent procedures, equal promotion opportunities, supportive organizational policies, and a culture that recognizes women’s leadership capacity.